Is rural nonfarm employment distress driven in Uttar Pradesh? Evidence from the NSSO rounds and PLF survey - Shadab Hashmi (Humanities & Social Sciences Communications)
Abstract Using National Sample Survey Organisation (NSSO) data, this study assesses the employment situation in Uttar Pradesh (UP), the most populous state in India, focusing on rural nonfarm employment. The primary objective of our study is to investigate the potential reasons for the movement of the labour force from farm to nonfarm activities over time in Uttar Pradesh. In UP, we observe that a higher proportion of workers are engaged in casual employment and employment growth stagnation in the rural manufacturing sector. We further observe that there is a declining proportion of people who are self-employed and regularly employed, and this situation has contributed to the casualisation of the rural workforce in UP. We also find that the average wages in agriculture are lower than those in non-agricultural activities. These observations point to the direction of distress in the agricultural sector, causing a shift in the workforce to a rural nonfarm sector. Casual employment in the rural nonfarm sector is considered to be low-paying employment compared to self-employment and regular employment outside agriculture, which are considered better-paying options. Hence, any movement of the workforce from agriculture to rural casual nonfarm employment is possibly driven by distress in the agricultural sector. Using a multinomial logit model, this study reveals that across all employment status categories, including agricultural labour, cultivators, nonfarm regular employment, nonfarm self-employment, and nonfarm casual employment, the likelihood of working in high-paying nonfarm regular and self-employment activities increases with better educational attainment, larger landholdings, and placement among the upper castes in social groups.